2011
DOI: 10.1088/0004-637x/743/1/41
|View full text |Cite
|
Sign up to set email alerts
|

Climate Instability on Tidally Locked Exoplanets

Abstract: Feedbacks that can destabilize the climates of synchronously rotating rocky planets may arise on planets with strong day-night surface temperature contrasts. Earth-like habitable planets maintain stable surface liquid water over geologic time. This requires equilibrium between the temperature-dependent rate of greenhouse-gas consumption by weathering, and greenhouse-gas resupply by other processes. Detected small-radius exoplanets, and anticipated M-dwarf habitable-zone rocky planets, are expected to be in syn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 110 publications
(153 reference statements)
2
74
0
Order By: Relevance
“…Sengupta (2015) argue that only a handful of the M-dwarfs with confirmed planets in the habitable zone meet the criteria for having Earth-like habitable conditions. Planets within the habitable zone of low-mass stars may also experience synchronous rotation and be tidally locked (Kasting et al 1993), leading to an unstable climate (Kite et al 2011).…”
Section: Habitabilitymentioning
confidence: 99%
“…Sengupta (2015) argue that only a handful of the M-dwarfs with confirmed planets in the habitable zone meet the criteria for having Earth-like habitable conditions. Planets within the habitable zone of low-mass stars may also experience synchronous rotation and be tidally locked (Kasting et al 1993), leading to an unstable climate (Kite et al 2011).…”
Section: Habitabilitymentioning
confidence: 99%
“…Also, GJ 581 is surrounded by at least four low mass planets with minimum masses of 1.9, 15.6, 5.4, and 7.1 M ⊕ , orbital radii of 0.03, 0.04, 0.07, and 0.22 AU, and eccentricities between 0.0 and 0.32, detected by radial velocity measurements (Bonfils et al 2005;Udry et al 2007;Mayor et al 2009;Forveille et al 2011). All these planets are within the tidal lock region of this M3 spectral type star (<0.25 AU) and hence are expected to be synchronously rotating and potentially undergoing atmospheric instabilities (Wordsworth et al 2011;Kite et al 2011). Planets GJ 581c and d are near and in the conventionally defined habitable zone (Selsis et al 2007), respectively.…”
Section: ) and Containmentioning
confidence: 99%
“…Fascinatingly, some recent work has suggested that the abundance of water in the mantle may be more important to geodynamics than the planetary mass (Korenaga 2010;O'Rourke & Korenaga 2012). Finally, even in the absence of other variations, tidally locked planets around M-stars should have very different carbon cycles from Earth due to the concentration of all incoming stellar flux on the permanent day side (Kite et al 2011;Edson et al 2012).…”
Section: Introductionmentioning
confidence: 99%